Science of Commerce, Political Economy and Civil Economy in Spanish Enlightenment (1714-1808) - Pablo CERVERA FERRI (Cuadernos Dieciochistas)
The chronology of economic ideas in Spanish Enlightenment is well known. However, the most accepted periodization does not fit with the evolution of moral philosophy and political economy in the 18th century, nor does it reflect the alternation in economic ideologies. After considering a joint articulation of national and generational approaches to the European economic thought, it seems important to differentiate the contents of political economy and civil economy to study the Spanish case. Below is a new periodization in five stages of enlightened economic thought in Spain: the time of colbertism and projectism (1714-1740), this of the learning of the science of commerce in Ensenada’s period (1740-1759), the emergence of political economy (1759-1773), the hegemony of the civil economy in late Enlightenment (1773-1792) and the return of political economy (1792-1808)